The Transcription Factor INDUCER OF CBF EXPRESSION1 Interacts with ABSCISIC ACID INSENSITIVE5 and DELLA Proteins to Fine-Tune Abscisic Acid Signaling during Seed Germination in Arabidopsis. Issue 7 (13th May 2019) - Hu, Yanru; Han, Xiao; Yang, Milian; Zhang, Minghui; Pan, Jinjing; Yu, Diqiu
Abstract : A transcriptional complex involving ABSCISIC ACID INSENSITIVE5 and its interacting partners maintains the appropriate level of abscisic acid signaling during seed germination. Abstract: ABSCISIC ACID INSENSITIVE5 (ABI5) is a crucial regulator of abscisic acid (ABA) signaling pathways involved in repressing seed germination and postgerminative growth in Arabidopsis ( Arabidopsis thaliana ). ABI5 is precisely modulated at the posttranslational level; however, the transcriptional regulatory mechanisms underlying ABI5 and its interacting transcription factors remain largely unknown. Here, we found that INDUCER OF CBF EXPRESSION1 (ICE1) physically associates with ABI5. ICE1 negatively regulates ABA responses during seed germination and directly suppresses ABA-responsive LATE EMBRYOGENESIS ABUNDANT6 ( EM6 ) and EM1 expression. Genetic analysis demonstrated that the ABA-hypersensitive phenotype of the ice1 mutant requires ABI5. ICE1 interferes with the transcriptional activity of ABI5 to mediate downstream regulons. Importantly, ICE1 also interacts with DELLA proteins, which stimulate ABI5 during ABA signaling. Disruption of ICE1 partially restored the ABA-hyposensitive phenotype of the della mutant, gai-t6 rga-t2 rgl1-1 rgl2-1, indicating that ICE1 functions antagonistically with DELLA in ABA signaling. Consistently, DELLA proteins repress ICE1's transcriptional function and the antagonistic effect of ICE1 on ABI5. Collectively, our study demonstrates that ICE1 antagonizes ABI5 and DELLA activity to maintain the appropriate level of ABA signaling during seed germination, providing a mechanistic understanding of how ABA signaling is fine-tuned by a transcriptional complex involving ABI5 and its interacting partners.